Sand consumption by Hoffmann´s two-toed sloth (Choloepus hoffmanni) at Cahuita National Park, Costa Rica - Durán-Apuy, Alejandro; Mora, José Manuel (Therya Notes, 2023)
Mineral licking has been reported in most herbivorous mammal taxa; however, the frequency of mineral lick use by Pilosa at ground level in the wild is rare. Hoffmann's two-toed sloth (Choloepus hoffmanni), an herbivorous Pilosa species, is nocturnal and arboreal. We present the first case of saline sand consumption by a Hoffmann's two-toed sloth in Costa Rica. The observations occurred at Cahuita National Park, Limón, Costa Rica, on October 11, 2022, at 21:20 hr. We observed a sloth hanging from the base of a water apple tree (Syzygium malaccense), with its head pointing downward upon discovery. Pictures and notes were taken during the event. The sloth securely suspended itself from a lateral branch of the main tree trunk. In this position, it brought its snout nearly in contact with the ground and proceeded to lick the saline sand several times. The sequence of actions, including suspension from the branch, intermittent licking, and recommencement of climbing, transpired over a span of approximately 5 minutes. The case we present here involves the consumption of saline sand rather than licking of rocks. Our observations were conducted during the nighttime when potential sloth predators are active. Clearly, further foundational research is needed to understand these basic aspects of sloth´s natural history. Mineral licking by sloths might constitute an infrequent conduct, although essential to provide individuals with vital nutrients.